Inteligencia de mercados para la exportación de café arábigo de la asociación AGROARTENAL de caficultores Rio Intag 'AACRI' del cantón Cotacachi provincia de Imbabura - Chávez Checa, Cinthya Nicole (2024)
The Rio Intag coffee association of the Cotacachi canton, province of Imbabura, is an association that works with the association of coffee producers of the locality. It has been established in the market for some years and is dedicated to the production of Arabica coffee, for its commercialization at local, provincial, national and international level. The objective of this research is to conduct market intelligence for the export of Arabica coffee from the Rio Intag Association, knowing that the company currently wishes to internationalize its product. The purpose of this research was to study the importance of market intelligence by identifying a target market to which the company is going to export. As a means of research, we worked with information from official websites such as TradeMap, ProEcuador, MPCEIP, among others. In addition, research instruments are applied to collect data in order to take the necessary measures to carry out the export plan and the implementation of the project. Arabica coffee covers the local demand and now with this research, it is determined that the target market is Germany, being the country that has the greatest acceptance\; it is also worth mentioning that the internationalization of several Ecuadorian companies and brands that have expanded into international markets has shown that there are opportunities to grow in specific niches.